A new and intriguing brown-spored Leucocoprinus species - Suarez, Juan M.; Gottlieb, Alexandra M.; Lechner, Bernardo E. (Phytotaxa, 2021)
Leucocoprinus brunneosporus sp. nov., collected at the Santa Catalina Reserve (Buenos Aires, Argentina), is proposed as a new species. We performed separate phylogenetic analyses of the nuclear rDNA large subunit (28S) and the complete nuclear rDNA internal transcribed spacer region (ITS) to establish the placement of the new species in the phylogeny of the Agaricaceae. This new species has a macromorphology similar to that of Lc. birnbaumii, but the spore print is light brown. Detailed descriptions and illustrations of the macro- and microscopic characters are provided.